EVALUASI MANAJEMEN TIM PERTANDINGAN DASH KARATE CLUB TAMAN-SIDOARJO - ARUM SETYANI, FEBRI ARUM (Jurnal Prestasi Olahraga, 2013)
On a competition event both on a regional or national event certainly it?s followed by teams that will follow that game either on few number of personnel or many. In order to carried out well, on time, smooth and secure, so it will need a good planning and it means that the existence of management or regulation on those compete team. Frequently on team management, when they have to arrange a competition, especially with number of arena that more than two, there will be a mess that cannot be avoided. It caused by the inappropriate in team management arrangement so it cause athlete and manager also the official experience many trouble during on the arena. The aim of this research is to evaluate competition team management that existed on ranting DASH Karate Club Taman-Sidoarjo. The object of this research are every component that include : 1) the execution of competition team management, 2) the planning of competition team, 3) the organization of competition game, 4) the implementation of competition game, and 5) the evaluation of competition result. Method in this analysis applying descriptive qualitative method, while data collecting process done by applying interview. Conclusion: 1) the execution of competition team management: competition team management that existed on DASH Karate Club Taman-Sidoarjo still using centralistic where only one man that thinking and working. 2) the planning of competition team: for the planning on DASH Karate Club Taman-Sidoarjo competition team.  3) the organization of competition game: have run well, the management structure have well ordered and there is no mean problem even the coach only coaching solely. 4) the implementation of competition game: the implementation of game have well directed, and well organized. 5) the evaluation of competition result: DASH Karate Club Taman-Sidoarjo always carried out evaluation in the end of activity that they executed. It have purpose to find out how far the activity have running appropriately.   Keywords: competition team management, DASH Karate Club Taman-Sidoarjo